Calcium sulfate beads made with antibacterial essential oil-water emulsions exhibit growth inhibition against Staphylococcus aureus in agar pour plates. - Allison N Hawkins; Sara J Licea; Sierra A Sleeper; Matthew C Swearingen (PLoS ONE)
Calcium sulfate bone void filler beads are fully absorbable in the body, and are often used in complicated orthopedic infection cases to release a relatively high dose of antibiotics locally to the body site over time. However, the antibiotic resistance crisis and/or inability to treat chronic biofilm infections remains to be a formidable and increasing health threat. In this report, we tested the hypothesis that plant essential oils (PEOs) with anti-staphylococcal qualities could inhibit the growth of Staphylococcus aureus (a major etiological agent of periprosthetic joint infection) in agar pour plates when infused in calcium sulfate beads. To begin, we conducted a screen of 57 single plant PEOs for anti-staphylococcal activity via disk diffusions assays. We observed that 55/57 of the PEOs had significant growth inhibitory activity compared to the null hypothesis, and 41/57 PEOs exhibited activity similar-to-or-higher-than a vancomycin minimum inhibitory control. When PEOs were infused in beads, we observed that 17/57 PEOs tested exhibited significant bacterial growth inhibition when encased in S. aureus-seeded agar compared to a null hypothesis of six millimeters (bead size). However, none of the PEO-beads had activity similar to a vancomycin bead control made according to a clinically relevant formula. To the best of our knowledge, this is the first report and screen of PEOs for growth inhibitory activity when infused in lab-made calcium sulfate beads. These data indicate that antibacterial PEOs warrant further investigations, and may be useful in developing new treatment strategies for periprosthetic joint infection.